2012
DOI: 10.1111/j.1365-2923.2011.04188.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of resilience and its relevance to medical training

Abstract: OBJECTIVES This article explores the concept of resilience and its potential relevance to medicine. It also looks at the dimensions of resilience and its ethical importance for effective professional practice, and considers whether a focus on resilience might be useful in medical training.METHODS An applied literature search was conducted across the domains of education, ethics, psychology and sociology to answer the research question: 'What is resilience and what might it mean for professional development in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
343
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(363 citation statements)
references
References 43 publications
12
343
0
8
Order By: Relevance
“…The dynamic nature of resilience sets it apart from other related psychologic traits, such as ''hardiness'' or ''mental toughness.'' 18 It has been shown to be protective from depression, other dimensions of distress, and tends to result in higher quality of life levels. 19 Dyrbye et al 19 found that health profession students with higher levels of resilience were more likely to create a collaborative learning environment, be part of good social support networks, and be better scaffolded by faculty members' involvement in their studies, but less likely to be engaged in employment during the course.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic nature of resilience sets it apart from other related psychologic traits, such as ''hardiness'' or ''mental toughness.'' 18 It has been shown to be protective from depression, other dimensions of distress, and tends to result in higher quality of life levels. 19 Dyrbye et al 19 found that health profession students with higher levels of resilience were more likely to create a collaborative learning environment, be part of good social support networks, and be better scaffolded by faculty members' involvement in their studies, but less likely to be engaged in employment during the course.…”
Section: Introductionmentioning
confidence: 99%
“…These include admitting students with interpersonal strengths that can be further developed in training, requiring reflection, creating a safe environment for failure, providing mentorship, and encouraging stress release. 31 Oliver, however, argues that resilience, like many other skills, must be developed on the job and that no amount of training in schools will increase it. 44 Some authors have discussed the role that schools can play in developing protective factors.…”
mentioning
confidence: 99%
“…Resilience has been defined as the ability of an individual to respond to stress in a healthy, adaptive way 7 and to meet problems as opportunities for growth 8 . Resilient students believe that what they do can have a positive impact on a situation 9 , and this was reflected in the experience of students in this setting.…”
Section: Can We Practice Medicine Congruently?mentioning
confidence: 99%